Actualization Of Customary Law (Living Law) As A Form Of Legal Reform In Indonesia - Alfin Aslichatul Ummah (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
The nation is the most important entity in a country; without it, there can be no state. In other words, the nation is the fundamental element of a state. The life of a nation is closely tied to its culture, as Aristotle put it,